On the presence of Anchistioides willeyi (Borradaile, 1899) (Decapoda: Caridea: Anchistioididae) in the Red Sea - Marin, Ivan (Zootaxa, 2009)
The palaemonoid family Anchistioididae Borradaile, 1915 includes a single genus Anchistioides Paulson, 1875 with four known valid species: Anchistioides compressus Paulson, 1875 (type species), A. willeyi (Borradaile, 1899), A. australiensis (Balss, 1921) and A. antiguensis (Schmitt, 1924). Borradaile (1915) suggested two more species within the genus Amphipalaemon Nobili, 1901 (a junior synonym of Anchisitioides Paulson), Amphipalaemon gardineri Borradaile, 1915 (= Anchistioides gardineri) and Amphipalaemon cooperi Borradaile, 1915 (= Anchistioides cooperi) which were later synonomyzed with Anchisitioides willeyi by Gordon (1935), who also suggested their conspecificity with Anchistioides australiensis. At the present time, Anchistioides australiensis is a valid species (Bruce, 1971; Chace & Bruce, 1993) based on specific morphological features such as the presence of sharp postorbital tooth, oblique distal lamela of scaphocerite and sharply produced spines on posterodorsal angles of sixth abdominal somite (see Bruce, 1971: fig. 9). The other Indo-Pacific species, Anchistioides compressus and A. willeyi, can be clearly identified by specific form of scaphocerite, the presence of a well marked blunt postorbital tubercle in A. willeyi which is absent in A. compressus (e.g., Bruce, 1971) and the number of ventral rostral teeth (3-4 large ventral rostral teeth present in A. willeyi while up to 8 small ventral rostral teeth in A. compressus (Paulson, 1875; Gordon, 1935)). Anchistioides antiguensis is clearly separated geographically being known only from the tropical Western Atlantic and Caribbean region (Schmitt, 1924; Holthuis, 1951; Wheeler & Brown, 1968; Martinez-Iglesias, 1986; Markham et al, 1990; Ramos-Porto et al, 1998; Cardoso, 2006).